MAPPING OF CONGENITAL ZIKA VIRUS SYNDROME, LOW BIRTH WEIGHT AND PREMATURITY IN BRAZIL: A SPATIAL ANALYSIS - Donateli, Cíntia Pereira; Braga, Gustavo Bastos; Assunção, Gabriel Gonçalves; Fernandes, Jefferson Souza; Costa, Glauce Dias da (Ra’e Ga: o Espaço Geográfico em Análise, 2024)
Knowledge and assessment of the consequences, mainly nutritional, that can affect children with Congenital Zika Virus Syndrome (CZS) still need to advance, mainly through spatial approaches that allow analyzing local vulnerabilities to generate better disease control and monitoring. This study aims to analyze the spatial distribution of CZS cases in Brazilian children and its association with low birth weight and prematurity. This is a retrospective ecological study with anonymized secondary data from the national public health event registration system (RESP-Microcephaly). To verify the existence of spatial association, the Local Indicators of Spatial Association (LISA), univariate and bivariate, were calculated. Therefore, we found that CZS is locally associated with low birth weight and prematurity. Of the 1,834 confirmed cases of CZS from 2015 to 2021 in Brazil that were part of the research universe, 31.2% of babies were born with low weight and 14.7% were premature. Furthermore, the results of LISA’s bivariate analysis show clusters of municipalities with a high incidence of CZS and a high incidence of low birth weight and prematurity in the Northeast region of the country. Finally, our findings demonstrated that there is a spatial association of CZS in Brazil and between CZS and childhood nutritional risks. Given the spatial analysis carried out, this study can contribute to the detection of vulnerable areas with a high incidence of CZS and thus assist in monitoring and evaluating their impacts.